49.6k views
5 votes
Solve the equation 4(x – 2) = 3x + 1.

User Aipo
by
4.6k points

2 Answers

5 votes

First distribute the four

4(x - 2) = 3x + 1 =

4x - 8 = 3x + 1

Now isolate the variable

4x - 8 = 3x + 1 =

4x = 3x + 9 =

x = 9

so your answer is nine

hoped this helped

User Loomchild
by
4.9k points
3 votes

Answer:

x=9

Explanation:

4(x – 2) = 3x + 1

Distribute 4x-8 = 3x+1

Subtract 3x from each side

4x -8-3x = 3x-3x + 1

x-8 =1

Add 8 to each side

x-8+8 = 1+8

x=9

User Rogare
by
4.7k points